LINKED AND MATCH: INTERMEDIARY COURSE LEARNING AND INDUSTRY NEEDS - Ahmad Kurniawan; Elly Malihah; Rini Andari (Sekolah Tinggi Pariwisata Mataram, 2022)
The problem of output in learning courses is often a barrier for students to get good jobs, as if it is not in accordance with the knowledge they have received from their teaching staff for the needs of the industry where they work. It is also included in the study of tourism science which in the end after students receive their education, of course they will become practitioners in it. Due to the lack of understanding in applying existing knowledge, it has an impact on decreasing the quality of performance. Of course, this is found from the data which shows that some of the tourism sub-sciences studied, such as in the dish supervision course, lack correlation with the needs of the restaurant and hospitality industry. The reason is because the teacher who provides the knowledge does not have the skills and abilities to teach according to the conditions in the field. Seeing from these problems, it is necessary to have a teaching and learning model that can be said to be linked and match in the world of tourism universities. Through a descriptive qualitative research method with an SLR (systematic literature review) approach in order to be able to elaborate on the problem in accordance with the purpose of this research, namely to find the phenomenon of linked and match meeting points between course learning and industrial needs.